GTF chromium (glocose tolerance factor) : its vitamin-like propieters could mean added protection against diabetes and heart disease - Passwater, Richard A (Good Health Guide, 1982)
The discovery of the role of GTF chromium in health is proving to be one of major importance. Research strongly suggests that GTF chromium is a protective factor against two of the three leading causes of death: heart disease and diabetes.